MIND MAPS IN EFL SPEAKING CLASSES: A CASE STUDY AT UNIVERSITY OF FOREIGN LANGUAGE STUDIES THE UNIVERSITY OF DANANG - Hoa, Phan Van; Trang, Ngo Thi Hien (VNU Journal of Foreign Studies; Vol 36 No 6DO - 10.25073/2525-2445/vnufs.4637, 2020)
Speaking, one of the two productive skills, has been paid much attention to by first-year students at the Faculty of English, University of Foreign Language Studies - The University of Danang (FE, UFLS - UD). There are a variety of strategies and techniques assisting EFL teachers and learners, and mind mapping technique is among these which could be implemented to improve teaching and learning performances in general and speaking skill in particular. Mind maps are being taken advantage of by EFL students in classes to improve their speaking skill. In this study, the researchers have assumed that mind maps have the facilitating impact on the oral speech performance of the first-year students at FE, UFLS - UD. We have conducted this research quantitatively and qualitatively whose data is from interview questions and a set of questionnaires for first-year students, and the researchers’ classroom observation. This is a case study which aims to explore the reality of using mind maps including the frequency, speaking stages, and freshmen’s attitudes when utilizing this technique to enhance this skill. Its suggestions could be applied in teaching and learning English speaking skill effectively.